Intensive Care Psychological Assessment Tool (IPAT): Turkish validity and reliability study - DUMAN, Berker (Turk J Med Sci, 2019)
BACKGROUND/AIM: It is of crucial importantance to be able to detect acute psychological distress in patients. The Intensive Care Psychological Assessment Tool (IPAT) was developed for this purpose in intensive care units. This study aims to evaluate the validity and reliability of the Turkish version of IPAT. MATERIALS AND METHODS: In total, 98 patients were included. To assess concurrent validity, the Intensive Care Experiences Scale (ICES) and the Hospital Anxiety Depression Scale were performed. Cronbach’s alpha coefficient was used to estimate internal consistency. Interitem and item-total score correlations were also performed. Sensitivity and specificity were derived for concurrent anxiety and depression. RESULTS: The internal reliability was good. Cronbach’s a = 0.85. Items were well-correlated, with an average interitem correlation of 0.38. The concurrent validity of IPAT was good. Correlation between IPAT scores, anxiety, depression, ICES, and the diagnosis of delirium were as follows, respectively: r = 0.61, P < 0.01, r = 0.54, P < 0.01, r = −0.66, P < 0.01, r = 0.37, P < 0.01. With a cutoff score of ≥ 6, IPAT showed 85% sensitivity and 61% specificity to detect concurrent anxiety, and 74% sensitivity and 82% specificity to detect concurrent depression [AUC = 0.77 (95% CI, 0.68–0.87) and 0.84 (95% CI, 0.76–0.92), respectively]. CONCLUSION: The Turkish version of IPAT was found to be a valid and reliable tool to assess acute psychological distress among patients in intensive care units.